EMPOWERING ENGLISH DEBATING COMMUNITY IN VOCATIONAL HIGHER EDUCATION: THE BRITISH PARLIAMENTARY FORMAT - Beni Wijaya; Nate Mandigo; Zakaria Zakaria; Leni Rohliah; Fathur Rohman; Balqis Cahaya Kautsar; Aditya Setiawan (SUBSERVE: Community Service and Empowerment Journal, 2026)
For students in vocational higher education, the development of critical thinking, public speaking, and argumentation abilities is crucial. Members of Politeknik Negeri Sriwijaya's English Debating Society (EDS) encountered difficulties in comprehending and using the British Parliamentary (BP) debate format, which is used in national and international competitions. Through organized training and mentorship exercises, this community service program sought to improve members' debate skills. 35 EDS members participated in the program, which included workshops, debate simulations, adjudication practice, and one-on-one feedback sessions. Pre-tests, post-tests, participant surveys, and observations were used to evaluate the program. The findings showed that participants' comprehension of BP debate structure, argument creation, rebuttal strategies, and Point of Information (POI) delivery had significantly improved. Between the pre-test and the post-test, the average participant score rose from 62.4 to 84.7. During debate sessions, participants also showed improved critical thinking abilities and increased self-assurance in public speaking. The program effectively improved vocational higher education students' debating skills and offered a long-lasting paradigm for debate instruction in student organizations.